Comparison of Symptom Severity and Progression in Advanced Cancer Patients Among Different Care Settings: A Secondary Analysis - Ryuto Shiraishi; Yoshiyuki Kizawa; Masanori Mori; Isseki Maeda; Yutaka Hatano; Hiroto Ishiki; Tomofumi Miura; Naosuke Yokomichi; Maiko Kodama; Keiko Inoue; Sen Otomo; Takashi Yamaguchi; et al. (Palliative Medicine Reports, 2023)
Background: Most people in Japan wish to spend their final days at home, but the majority fail to do so; earlier studies indicated a more pronounced worsening of symptoms if treated at home. Objectives: This study compared the prevalence of symptom worsening and explored associated factors between patients with advanced cancer receiving palliative care in palliative care units (PCUs) and at home. Design: We conducted a secondary analysis of two multicenter, prospective cohort studies involving patients with advanced cancer receiving palliative care in PCUs or at home. Setting/Subjects: One study was conducted at 23 PCUs (January to December 2017) and the other on 45 palliative home care services (July to December 2017) in Japan. Measurements: Symptom changes were categorized as stable, improved, or worse. Results: Of the 2998 registered patients, 2877 were analyzed. Among them, 1890 patients received palliative care in PCUs, and 987 at home. Patients receiving palliative care at home were more likely to have worsening of pain (17.1% vs. 3.8%; p?<?0.001) and drowsiness (32.6% vs. 22.2%; p?<?0.001) than those in PCUs. By multivariate logistic regression analysis, palliative care at home was significantly associated with worsening of the Palliative Prognostic Index dyspnea subscale in the unadjusted model (odds ratio, 1.42 [95% confidence interval, 1.08?1.88]; p?=?0.014) but not for any symptoms in the adjusted model. Conclusions: After adjusting for patient background, the prevalence of symptom worsening was not different between patients with advanced cancer receiving palliative care at home and in PCUs.